KAJIAN YURIDIS RESTORATIVE JUSTICE TERHADAP PELAKTINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN ORANG MENINGGAL - Muhammad Andika Bahri; Rizkan zulyadi; Wessy Trisna (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
Restorative justice is an approach to settling a case by means of deliberation and consensus to restore the parties, especially the victims. The author reviews the decision number 478 / Pid.Sus / 2017 / Pn.Mdn. In the verdict it has an elemental value from a restorative justice, namely the existence of an apology from the victim, restitution or ransom of compensation, and relief of criminal penalties. According to Law Number 22 Year 2009 concerning Road Traffic and Transportation, the regulation of legislation and the consequences of compensation laws or peace efforts to victims of traffic accidents. The status of the related party in the case of a traffic accident after giving compensation to the victim or his heirs is not miscarried as stipulated in article 235 of Law Number 22 Year 2009 concerning Road Traffic and Transportation. The role of law enforcers in providing compensation to victims of traffic accidents is not really needed unless there is a special request from one of the parties.